Molecular dynamics study of the pore formation in single layer graphene oxide by a thermal reduction process. Issue 20 (14th May 2021) - Raffone, Federico; Savazzi, Filippo; Cicero, Giancarlo
Abstract : The shape/dimension of the oxidized clusters and the process temperature were found to be the main factors affecting pore formation in GO membranes produced with a thermal reduction process. Abstract : Nanoporous graphene is considered the next-generation material for reverse osmosis water desalination providing both high water permeability and almost complete salt rejection. The main problem with graphene is the difficulty of synthesizing membranes with a consistent subnanometer pore size distribution. A recently proposed solution involves processing as-grown graphene oxide (GO) monolayers via a mild temperature annealing pre-treatment causing GO functional groups to cluster into small oxidized islands. A following harsh thermal reduction process creates pores only in the small oxidized regions. However, a suitable relationship between the area of the GO islands and the pore dimension is still missing. Here, we study in detail the effects of such a thermal reduction process on the graphene oxide sheet by means of molecular dynamics simulations, particularly highlighting and analysing the process parameters affecting the final pore area. Besides proving that epoxides represent the most suitable functional group to induce carbon removal and, thus, pore generation in reduced GO, we find a twofold way to achieve control over the pore size: tuning the dimension and shape of the initial clustered GO areas or changing the harsh reduction process temperature. An accurate balance of these parameters consistently gives rise to targeted pore dimensions in graphene membranes.